Complete Genome Sequence of Elephant Endotheliotropic Herpesvirus 1A - Ling, Paul D.; Reid, Jeffrey G.; Qin, Xiang; Muzny, Donna M.; Gibbs, Richard; Petrosino, Joseph; Peng, RongSheng; Zong, Jian-Chao; Heaggans, Sarah Y.; Hayward, Gary S. (Genome announcements (Washington, DC), 2013)
Elephant endotheliotropic herpesvirus 1A is a member of the Proboscivirus genus and is a major cause of fatal hemorrhagic disease in endangered juvenile Asian elephants worldwide. Here, we report the first complete genome sequence from this genus, obtained directly from necropsy DNA, in which 60 of the 115 predicted genes are not found in any known herpesvirus.